Canonical discriminant analysis projected in standard metric space as an optimal method for determining differences in motor dimensions between judo and karate athletes - Popovic, M.; Savic, V.; Bojovic, M. (Facta Universitatis: Series Physical Education and Sport, 2016)
The motor tests, as standardized procedures, represent the most important source of information about the level and development of motor abilities of a subject, which is needed in the process of talent identification and selection. The main aim of the current research was to determine the differences in motor dimensions between judo and karate athletes. The sample of participants consisted of 200 athletes (100 judokas and 100 karatekas of both sexes) aged 18 to 27. To assess motor abilities, the researchers used 15 motor tests defined as the mechanism for movement structuring, mechanism for muscle tone regulation and synergistic regulation, mechanism for regulation of excitation intensity, and the mechanism for the regulation of excitation duration. The results of the discriminant analyses of motor variables indicate that the tested athletes in relation to the preferred branch of sport differ significantly. Based on the values and signs of the centroids of the groups, it can be concluded that judokas have greater strength and coordination, while karatekas have better segmentary speed of the arms and flexibility, which is consistent with the requirements of the two sports.